Pro Sexto Roscio - Cicero, Marcus Tullius (Cambridge Greek and Latin classics., 2010)
"Sextus Roscius was murdered in Rome some months after the official end of the Sullan proscriptions on 1 June 81 BC. The case was tried early the following year with a young Cicero acting as defense counsel in his first criminal case for the accused son. Though a novice, Cicero was able to tap into the public anger over the uncontrolled killing and looting of the proscriptions and channel it against the men behind the prosecution, T. Roscius Magnus and T. Roscius Capito. Cicero won a career-making victory, establishing his reputation as a formidable advocate. This, the first new edition of the work in English to be published for almost a century, provides a Latin text and commentary updated to take account of advances in the study of the Latin language as well as Roman institutions, law and society. It is suitable for use with upper-level undergraduates and graduate students"--Provided by publisher.